2021
DOI: 10.3390/cells10030602
|View full text |Cite
|
Sign up to set email alerts
|

Growth Arrest-Specific Gene 6 Administration Ameliorates Sepsis-Induced Organ Damage in Mice and Reduces ROS Formation In Vitro

Abstract: Sepsis is a widespread life-threatening disease, with a high mortality rate due to inflammation-induced multiorgan failure (MOF). Thus, new effective modulators of the immune response are urgently needed to ameliorate the outcome of septic patients. As growth arrest-specific gene 6 (Gas6)/Tyro3, Axl, MerTK (TAM) receptors signaling has shown immunomodulatory activity in sepsis, here we sought to determine whether Gas6 protein injection could mitigate MOF in a cecal slurry mouse model of sepsis. Mice, divided i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…These observations suggest the possibility that Gas6 could cause pulmonary epithelial cell damage similarly to the VE cell damage that we observed in our previous study ( 20 ). On the other hand, combined treatment with Gas6 and antibiotics ameliorates sepsis-induced organ damage in mice with sepsis induced by intraperitoneal injection of bacterial aliquots of cecal slurry, suggesting that intravenous injection of Gas6 may be a viable therapeutic option in sepsis ( 41 ). Here, we found that plasma Gas6 and sMer concentrations were significantly greater in patients with septic ALI/ARDS compared with those in healthy controls (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…These observations suggest the possibility that Gas6 could cause pulmonary epithelial cell damage similarly to the VE cell damage that we observed in our previous study ( 20 ). On the other hand, combined treatment with Gas6 and antibiotics ameliorates sepsis-induced organ damage in mice with sepsis induced by intraperitoneal injection of bacterial aliquots of cecal slurry, suggesting that intravenous injection of Gas6 may be a viable therapeutic option in sepsis ( 41 ). Here, we found that plasma Gas6 and sMer concentrations were significantly greater in patients with septic ALI/ARDS compared with those in healthy controls (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research suggests that Gas6 signaling has a protective role in mice models of multi-organ dysfunction syndrome, ALI in sepsis, and ischemia/reperfusion-induced ALI [ 28 , 29 , 30 , 31 ]. In contrast, Gas6 or Mer deficiency is protective against silica-induced lung inflammation and fibrosis in mice [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…TAM signaling is crucial in modulating the innate immunity. Previous studies indicate that Gas6/Mer or Axl signaling provides a protective effect in mouse models of multi-organ failure syndrome and acute lung injury, (Salmi et al 2021 ; Kim et al 2021 ; Peng et al 2019 ), and acute liver injury (Zagórska et al 2020 ). In contrast, genetic deficiency of Gas6 or Mer in mice provides protection against pulmonary inflammation and fibrosis triggered by silica exposure.…”
Section: Introductionmentioning
confidence: 99%